PERAN DIGITALISASI DALAM MANAJEMEN SUMBER DAYA MANUSIA DI PERGURUAN TINGGI - Adenuddin Alwy, Muhammad; Sari Baso, Rachmie (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Digitalization has driven significant changes in human resource management in higher education institutions, particularly in employee data management, work processes, and personnel decision-making. This study aims to analyze the role of digitalization in human resource management in universities and to describe its implementation and implications for HR effectiveness. The research uses a qualitative method with a literature study approach by reviewing and analyzing relevant scientific journals. The analysis technique involves identifying, classifying, comparing, and synthesizing the main ideas from each source. The results indicate that digitalization through e-Human Resource Management and HRIS improves administrative efficiency, data integration, performance transparency, and supports competency development and workforce planning for academic and administrative staff. The main challenges relate to users’ digital competence and institutional policy support.